Time course and mechanisms of the anti‐hypertensive and renal effects of liraglutide treatment. Issue 3 (15th October 2014) - von Scholten, B. J.; Lajer, M.; Goetze, J. P.; Persson, F.; Rossing, P.
Abstract Aims Glucagon‐like peptide–1 receptor agonist studies have revealed clinically significant reductions in systolic blood pressure (SBP). The aim was to investigate the time course of the anti‐hypertensive effect of liraglutide treatment and potential underlying mechanisms. Methods We used an open‐label, single‐centre trial; 31 participants with Type 2 diabetes and hypertension completed the study. All participants were treated with liraglutide escalated to a maximum dose of 1.8 mg/day for 7 weeks, followed by a 21–day washout period. The primary outcome was a change in 24–h SBP. Results Twenty‐four‐h SBP increased by 10 mmHg on day 3 (P = 0.008) and 7 mmHg on day 7 (P = 0.033, 0.6 mg/day). On day 29, (1.8 mg/day), 24–h SBP was 7 mmHg lower compared with baseline (P = 0.11). Following the treatment period (day 49) and after washout (day 70), 24–h BP was equivalent to baseline. In addition, extracellular volume (ECV) was reduced by 2.0 l [95% confidence interval (CI) = 1.0–3.1 l, P < 0.001] and midregional‐pro‐atrial natriuretic peptide (MR–proANP) was reduced by 20% (95% CI = 12–28%, P < 0.001). Also, urinary albumin excretion declined by 30% (95% CI = 12–44%, P = 0.003), GFR by 11 ml/min/1.73 m2 (95% CI = 7.2–14.4 ml/min/1.73 m2, P < 0.001) and fractional albumin excretion by 29% (95% CI = 3–48%, P = 0.032). Conclusions Liraglutide treatment was associated with an initial increase in 24–h SBP, followed by a 7 mmHg reduction after escalation to 1.8 mg/day. This effect subsided after 4 weeks of maximum dose. Reductions in ECV and MR–proANP may explain the anti‐hypertensive potential. Liraglutide treatment was associated with reversible reductions in albuminuria and GFR, which has to be confirmed in randomized trials.